Pcr-Based Detection of Chicken and Cattle Meat Targeting Cytochrome B Gene As Affected By Heating and Mixing of Meat - ABDUL-HASSAN, ISMAIL ABDUL-REDHA; TAUMA, JALAL ALI (Science Journal of University of Zakho, 2013)
This study was conducted to examine the effects of heating and mixing of cattle and chicken meat on their identification by PCR targeting cytochrome b gene using species-specific primers. In addition to simplex PCR, multiplex-PCR was used for detection in meat mixtures. Five samples of cattle meat and five samples of chicken meat were subjected to 80, 90, 100, 110 and 120 C for 20 minutes. The results of PCR targeting cytochrome b gene showed that all heat treatment groups of cattle and chicken meat were identical. After mixing equal quantities of cattle and chicken, ten samples were selected from different locations in the mixture. Results showed that 50 % of samples were present both cattle and chicken, whereas, only 30 % of samples were present cattle only, in addition, only 20 % of samples were present chicken only. The results of this study confirm that DNA was unaffected by heating up to 120 C for 20 minutes and refer to the importance of increasing sample numbers and sites of tested meat mixtures.